2019
DOI: 10.1128/aem.01579-19
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Specific Differences in Survival of Campylobacter spp. in Naturally Contaminated Turkey Feces and Water

Abstract: Campylobacter jejuni and Campylobacter coli are leading causes of human foodborne illness, with poultry as a major vehicle. Turkeys are frequently colonized with Campylobacter, but little is known about Campylobacter survival in turkey feces, even though fecal droppings are major vehicles for Campylobacter within-flock transmission as well as for environmental dissemination. Our objective was to examine survival of Campylobacter, including different strains, in freshly excreted feces from naturally colonized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
(69 reference statements)
5
6
0
Order By: Relevance
“…Previous studies of turkey and swine farms in eastern North Carolina as well as wildlife and cattle in the same region, using the same culture conditions as those employed here, revealed a high prevalence of Campylobacter ; Arcobacter was not isolated from those samples, which yielded exclusively C. jejuni or C. coli ( 14 , 17 19 , 21 , 24 , 25 ). In the floodwater samples analyzed in the current study, Campylobacter prevalence was low (1.0%) in contrast to the overall high prevalence (73.5%) of Arcobacter .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Previous studies of turkey and swine farms in eastern North Carolina as well as wildlife and cattle in the same region, using the same culture conditions as those employed here, revealed a high prevalence of Campylobacter ; Arcobacter was not isolated from those samples, which yielded exclusively C. jejuni or C. coli ( 14 , 17 19 , 21 , 24 , 25 ). In the floodwater samples analyzed in the current study, Campylobacter prevalence was low (1.0%) in contrast to the overall high prevalence (73.5%) of Arcobacter .…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, this team was already in place and readily poised to collect and analyze Hurricane Florence-associated floodwater samples as soon as it became logistically possible and safe to reach impacted areas. The original objective of the current study was to assess the prevalence of Campylobacter jejuni and Campylobacter coli in the floodwaters and allow comparisons with genotypic data collected over several years of investigation of these zoonotic pathogens in food animals and wildlife in this region ( 14 , 17 25 ). However, in the course of the study, we detected numerous samples positive for Arcobacter , and therefore, we undertook the additional objective of characterizing the prevalence and genotypic diversity of Arcobacter from the hurricane-associated floodwaters.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying reasons remain to be elucidated, and may reflect regional differences in the C. jejuni and C. coli strains colonizing turkey flocks. Regional influences were also suggested in the study of strains from Italy [ 39 ], as well as by our findings with C. jejuni ST-1839, which appears to be predominant in turkeys in North Carolina according to the current study and previously [ 34 , 35 , 46 ], while not encountered in isolates from turkey farms in Ohio [ 45 ]. In fact, of the 22 STs detected in the turkey farms in Ohio [ 45 ], only three—the C. coli STs 889 and 1017, and the C. jejuni ST-2934—were shared with those in our study, and none of the STs in the current study were shared with those from the turkey farms in Italy [ 39 ].…”
Section: Discussionsupporting
confidence: 87%
“…The AMR pattern of C. jejuni influences its survival by providing an improved biological fitness. Good et al (2019) demonstrated that multi-drug resistant C. jejuni strains were among the longest surviving isolates to antibiotherapy ( Luo et al, 2005 ; González and Hänninen, 2012 ; Good et al, 2019 ). Furthermore, the ability of FQ-resistant strains to persist in the environment (e.g., in poultry production), after the removal of the selective pressure, was also demonstrated ( Price et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%